KONSTRUKSI KEARIFAN LOKAL MASYARAKAT PETANI HUTAN RAKYAT DALAM PEMANFAATAN DUWET (Syzygium cumini Linn) - Maria Palmolina; Eva Fauziyah (Jurnal Penelitian Sosial dan Ekonomi Kehutanan, 2018)
One of the forms of ethnoecological tradition performed for generations by the people of the Triwidadi Village, Pajangan, DI Yogyakarta is the utilization of forest resources “duwet” (Syzygium cumini Linn) as a medicinal plant. However, these values and local wisdom received less recognition and appreciation from the government, especially to be considered as a basis in the formulation of forest management policies in Java. The aims of the study are to construct local wisdom in the utilization of duwet as a form of physical culture of an institutionalized knowledge system.by using cognitive ethnographic method. This semi-quantitative research is focused to seek sociological explanation of cultural knowledge systems and duwet utilization process. Duwet habitat is in natural forest, secondary forest, and garden-yard, describes the form of changes in the environmental adaptation and social processes of forest resource utilization. The results showed that there is a symbolic interaction in the utilization of duwet consisting of constitution, cognitive, assessment and disclosure feeling symbols. In the construction of local knowledge, the utilization of duwet reflects six essential elements of ethnoecology, namely local resources, local knowledge, local value, local skills, local solidarity groups, and mechanisms of local decision-making.